Improved lipid production via fatty acid biosynthesis and free fatty acid recycling in engineered Synechocystis sp. PCC 6803 - Kamonchanock Eungrasamee; Rui Miao; Aran Incharoensakdi; Peter Lindblad; Saowarath Jantaro (Biotechnology for Biofuels, 2019)
Abstract Background Cyanobacteria are potential sources for third generation biofuels. Their capacity for biofuel production has been widely improved using metabolically engineered strains. In this study, we employed metabolic engineering design with target genes involved in selected processes including the fatty acid synthesis (a cassette of accD, accA, accC and accB encoding acetyl-CoA carboxylase, ACC), phospholipid hydrolysis (lipA encoding lipase A), alkane synthesis (aar encoding acyl-ACP reductase, AAR), and recycling of free fatty acid (FFA) (aas encoding acyl–acyl carrier protein synthetase, AAS) in the unicellular cyanobacterium Synechocystis sp. PCC 6803. Results To enhance lipid production, engineered strains were successfully obtained including an aas-overexpressing strain (OXAas), an aas-overexpressing strain with aar knockout (OXAas/KOAar), and an accDACB-overexpressing strain with lipA knockout (OXAccDACB/KOLipA). All engineered strains grew slightly slower than wild-type (WT), as well as with reduced levels of intracellular pigment levels of chlorophyll a and carotenoids. A higher lipid content was noted in all the engineered strains compared to WT cells, especially in OXAas, with maximal content and production rate of 34.5% w/DCW and 41.4 mg/L/day, respectively, during growth phase at day 4. The OXAccDACB/KOLipA strain, with an impediment of phospholipid hydrolysis to FFA, also showed a similarly high content of total lipid of about 32.5% w/DCW but a lower production rate of 31.5 mg/L/day due to a reduced cell growth. The knockout interruptions generated, upon a downstream flow from intermediate fatty acyl-ACP, an induced unsaturated lipid production as observed in OXAas/KOAar and OXAccDACB/KOLipA strains with 5.4% and 3.1% w/DCW, respectively. Conclusions Among the three metabolically engineered Synechocystis strains, the OXAas with enhanced free fatty acid recycling had the highest efficiency to increase lipid production.